2011
DOI: 10.3109/10929088.2011.578367
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and diagnostic yield of CT-guided stereotactic liver biopsy of primary and secondary liver tumors

Abstract: Objective: CT-guided biopsy still plays a decisive role in the management of liver tumors, especially if the lesions are not visible or accessible by ultrasound. As CT-guided stereotaxy appears to be a very accurate targeting technique, the aim of this study was to evaluate the targeting accuracy, diagnostic yield, and complications of CT-guided stereotactic liver biopsy of primary and secondary liver tumors. Methods and Materials: Prior to stereotactic liver biopsy, patients under general anesthesia were immo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Needle placement is performed with high accuracy. A median lateral error of needle placement of 2.5 mm was reported (58). Haidu et al reported a 1-and 3-year survival rate of 91% and 71% in 11 patients after SRFA (34), with an estimated median overall survial of 60 months.…”
Section: Stereotactic Radiofrequency Ablationmentioning
confidence: 99%
“…Needle placement is performed with high accuracy. A median lateral error of needle placement of 2.5 mm was reported (58). Haidu et al reported a 1-and 3-year survival rate of 91% and 71% in 11 patients after SRFA (34), with an estimated median overall survial of 60 months.…”
Section: Stereotactic Radiofrequency Ablationmentioning
confidence: 99%
“…This is the reason why many needle-based interventions are nowadays carried out with the help of ultrasound (US) or computed tomography (CT) scanners. 2,3 Although US is compact, cheap, and widely available, deep structures within the body, especially underneath bones, are hardly visible. [4][5][6] In contrast, CT enables an appropriate representation of the whole operating area.…”
Section: Introductionmentioning
confidence: 99%
“…For that reason our study focused on the technical success of lesion targeting. An interesting alternative approach has been studied by Schullian et al [29] who evaluated CT-guided stereotactic liver biopsy by coupling an optical-based navigation system and a stereotactic aiming device. The authors reported high targeting accuracy data in terms of lateral and angular errors, and a diagnostic yield of 97.8 % that was even slightly higher than that in our cohort study.…”
mentioning
confidence: 99%